1999
DOI: 10.1161/01.atv.19.2.321
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Phosphorylation Is Essential for the Turnover of Neutral Lipid and the Second Stage Assembly of Triacylglycerol-Rich ApoB-Containing Lipoproteins in Primary Hepatocyte Cultures

Abstract: Abstract-Primary hepatocytes cultured in a medium supplemented with amino acids and lipogenic substrates responded to increased extracellular glucose by increasing the secretion of VLDL apoB. This effect was accompanied by an increased secretion of VLDL triacylglycerol (TAG) derived from endogenous stores. Glucose also stimulated intracellular TAG mobilization via the TAG lipolysis/esterification cycle. All these effects were abolished in the presence of mannoheptulose (MH), an inhibitor of glucose phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 78 publications
0
17
3
Order By: Relevance
“…Additionally, insulin is a well-known acute inhibitor of VLDL secretion (52)(53)(54), and insulin resistance is associated with increased VLDLtriglyceride and apoB secretion (9 -11). Furthermore, recent data has shown that phosphorylation of glucose is also of importance in the regulation of assembly and secretion of triglyceride-containing VLDL (19). In our study, surprisingly, we did not find increased VLDL-triglyceride secretion in the S4048-treated rats.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Additionally, insulin is a well-known acute inhibitor of VLDL secretion (52)(53)(54), and insulin resistance is associated with increased VLDLtriglyceride and apoB secretion (9 -11). Furthermore, recent data has shown that phosphorylation of glucose is also of importance in the regulation of assembly and secretion of triglyceride-containing VLDL (19). In our study, surprisingly, we did not find increased VLDL-triglyceride secretion in the S4048-treated rats.…”
Section: Discussioncontrasting
confidence: 57%
“…Overexpression of hepatic glucokinase also leads to hyperlipidemia in fed rats (18). Brown et al (19) showed that the phosphorylation process is important for regulation of assembly and secretion of triglyceride-containing VLDLs by hepatocytes. Little is known about the mechanisms underlying the apparent paradox that hyperlipidemia de-velops in conditions associated with high as well as low G6Pase activity, i.e., diabetes and GSD.…”
mentioning
confidence: 99%
“…Therefore, in the setting of increased NEFA flux, hyperglycaemia may enhance TG synthesis. Along these lines, it has been indicated that glucose could influence the bulk lipid addition step of VLDL assembly [43]. Another potential source of liver TG is de novo lipogenesis [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…These FAs are removed by liver and esterified into TG that may be assembled into VLDL-TG for export. FA may also be derived within liver by de novo synthesis (24)(25)(26). Mature VLDL particles are assembled in two steps (27): complexes form between lipids and apoB in the rough endoplasmic reticulum (ER) to form a primary VLDL particle, and these fuse with a separately formed "apoB-free" lipid particle fashioned in smooth ER (28).…”
mentioning
confidence: 99%